The Role of Buzz Marketing in Increasing Attention Towards Green Products, ModeratingRole of ’Shockvertising’ - HASHEM, DR. TAREQ N. (The journal of contemporary issues in business and government, 2021)
Current study aimed at examining the influence of using buzz marketing on drawing attention of customers towards green products through the moderating influence of shockvertising. Study employed elements of buzz marketing (buzzing, seeding, and motivation). Depending on quantitative approach, a questionnaire was uploaded online through Google forms and (456) responses were collected. Utilizing SPSSV26 program, results of study indicated that buzz marketing can have the ability to draw customers’ attention towards green products through the moderating influence of shockvertising; results also indicated that buzz marketing through shockvertising can motivate individuals towards getting the product in order to experience what others have based on WoM through social media. Study recommended that buzz marketing is all about presenting what is unusual, but tackling the forbidden within the society as an approach to buzz marketing won’t be a good choice for the organization.